Projected changes in extreme precipitation intensity and dry spell length in Côte d’Ivoire under future climates - Yapo, Assi Louis Martial; Diawara, Adama; Kouassi, Benjamin K.; Yoroba, Fidèle; Sylla, Mouhamadou Bamba; Kouadio, Kouakou; Tiémoko, Dro T.; Koné, Dianikoura Ibrahim; Akobé, Elisée Y.; Yao, Kouassi P. A. T. (Theoretical and applied climatology, 2020)
This study analyzes projected changes in seasonal extreme precipitation intensity and dry spell length in the investigation area (Côte d’Ivoire) under RCP4.5 and RCP8.5 forcing scenarios. To this end, a multi-model ensemble of fourteen CORDEX-Africa regional climate model simulations is used during the three stages of the West African Monsoon (WAM) season (April–June (AMJ), July–September (JAS), and October–December (OND)). The results indicate that Côte d’Ivoire is subject to a robust increase of cumulative intensity of precipitation associated with an amplification of extreme precipitation events during the WAM. In particular during JAS, a substantial increase in extreme precipitation reaching up to 50–60% compared to the reference mean value prevails in the western and coastal areas in the far future and under the RCP8.5 scenario. In addition, AMJ season is dominated by an increase in dry spell length of about 12% and 17% in the near future and 20% and 30% in the far future in the entire country under RCP4.5 and RCP8.5 scenarios, respectively, albeit considerable uncertainties. OND considered as the post-monsoon season is mostly characterized by a robust decrease in dry spell length more marked in the southwest in the RCP8.5 scenario during the far future. These results suggest that agricultural production and particularly cocoa plantations in the southwestern regions could be at the risk of flooding events and that water stress remains a threat for cocoa, coffee, and other cash crop plantations in the eastern regions.